Insight into Vaccine Development for Alphacoronaviruses Based on Structural and Immunological Analyses of Spike Proteins - Shi, Yuejun (J Virol, 2021)
Coronaviruses that infect humans belong to the Alphacoronavirus (including HCoV-229E) and Betacoronavirus (including SARS-CoV and SARS-CoV-2) genera. In particular, SARS-CoV-2 is currently a major threat to public health worldwide. The spike (S) homotrimers bind to their receptors via the receptor-binding domain (RBD), which is a major target to block viral entry. In this study, we selected Alphacoronavirus (HCoV-229E) and Betacoronavirus (SARS-CoV and SARS-CoV-2) as models. Their RBDs exist two different conformational states (“lying” or “standing”) in the prefusion S-trimer structure. Then, the differences in the immune responses to RBDs from these coronaviruses were analyzed structurally and immunologically. Our results showed that more RBD-specific antibodies (antibody titers: 1.28 × 10(5) and 2.75 × 10(5), respectively) were induced by the S-trimer with the RBD in the standing state (SARS-CoV and SARS-CoV-2) than the S-trimer with the RBD in the lying state (HCoV-229E; antibody titers: <500), and more S-trimer-specific antibodies were induced by the RBD in the SARS-CoV and SARS-CoV-2 (antibody titers: 6.72 × 10(5) and 5 × 10(5), respectively) than HCoV-229E (antibody titers: 1.125 × 10(3)). Besides, we found that the ability of the HCoV-229E RBD to induce neutralizing antibodies was lower than S-trimer, and the intact and stable S1 subunit was essential for producing efficient neutralizing antibodies against HCoV-229E. Importantly, our results reveal different vaccine strategies for coronaviruses, and S-trimer is better than RBD as a target for vaccine development in Alphacoronavirus. Our findings will provide important implications for future development of coronavirus vaccines. IMPORTANCE Outbreaks of coronaviruses, especially SARS-CoV-2, pose a serious threat to global public health. Development of vaccines to prevent the coronaviruses that can infect humans has always been a top priority. Coronavirus spike (S) protein is considered a major target for vaccine development. Currently, structural studies have shown that Alphacoronavirus (HCoV-229E) and Betacoronavirus (SARS-CoV and SARS-CoV-2) RBDs are in “lying” and “standing” states in the prefusion S-trimer structure. Here, we evaluated the ability of S-trimer and RBD to induce neutralizing antibodies among these coronaviruses. Our results showed that the S-trimer and RBD are both candidates for subunit vaccines in Betacoronavirus (SARS-CoV and SARS-CoV-2) with an RBD standing state. However, for Alphacoronavirus (HCoV-229E) with an RBD lying state, the S-trimer may be more suitable for subunit vaccines than the RBD. Our results will provide novel ideas for the development of vaccines targeting S protein in the future.